Modern technologies of refractive lenticular extraction in the correction of myopia - I. A. Mushkova; S. V. Kostenev; N. V. Maychuk; M. R. Obraztsova; P. O. Nosirov; I. S. Malyshev (Российский офтальмологический журнал)
Purpose. To analyze the clinical and functional results of refractive lenticular extraction using ReLEx SMILE® and CLEAR® technologies in patients with moderate and high myopia.Materials and methods. 160 patients (160 eyes) aged 18 to 36 years diagnosed with moderate or high myopia, who had binocular vision, average keratometry parameters (43.0–45.0 D), and no contraindications to laser vision correction were operated according to the technology of refractive extraction of lenticula followed up 1 and 3 months after surgery. The patients were divided into 2 groups: (1) SMILE, which included 80 eyes of patients operated with the femtosecond laser VisuMax 500; and (2) CLEAR, including 80 eyes of patients operated using the femtosecond laser FEMTO LDV Z8. Both types of surgery were performed according to standard protocols.Results. No intraoperative complications were recorded. The analysis of clinical and functional parameters in the correction of myopia using the technology of refractive lenticular extraction performed with VisuMax and LDV Z8 femtosecond lasers demonstrated high and comparable efficiency, safety, predictability and stability.Conclusion. Both technologies of refractive lenticular extraction can be recommended for wide clinical use in the correction of moderate and high myopia.